2012
DOI: 10.2478/v10213-012-0018-0
|View full text |Cite
|
Sign up to set email alerts
|

P-Wave Dispersion in Prediction of Maintenance of Sinus Rhythm After an Electrical Cardioversion of Atrial Fibrillation in Dogs

Abstract: The aim of this study was to demonstrate the diagnostic accuracy of P-wave dispersion in predicting recurrence of atrial fibrillation in dogs with sinus rhythm restoration after external cardioversion. The study was performed on 15 dogs, which underwent electrical external cardioversion after atrial fibrillation. Nine-lead surface electrocardiogram of each dog was recorded 1 min after the cardioversion process to measure the P-wave duration. Dogs with recurrent atrial fibrillation had significantly higher P-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In this study, P wave durations were measured over 11 leads, whilst in the study by Michlik et al, only 9 leads were used [ 40 ]. Previous studies in animals have used either six or nine leads to calculate the P wave indices [ 37 , 38 , 39 ]. However, it has been reported that the use of adjacent leads with shared vectorial orientation may provide greater sensitivity for distinguishing inhomogeneity of atrial activation [ 46 ], and it has been suggested that ECGs with ≤nine leads should be excluded from the analysis [ 9 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, P wave durations were measured over 11 leads, whilst in the study by Michlik et al, only 9 leads were used [ 40 ]. Previous studies in animals have used either six or nine leads to calculate the P wave indices [ 37 , 38 , 39 ]. However, it has been reported that the use of adjacent leads with shared vectorial orientation may provide greater sensitivity for distinguishing inhomogeneity of atrial activation [ 46 ], and it has been suggested that ECGs with ≤nine leads should be excluded from the analysis [ 9 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported the use of P wave indices in veterinary medicine [ 37 , 38 , 39 , 40 , 41 , 42 ]. In dogs, Pd has been shown to be significantly increased in those with chronic valvular disease and disturbances of supraventricular conduction [ 38 , 42 ] and was also found to be a useful predictor of arrhythmia recurrence following electrical cardioversion of AF [ 39 ]. In horses, only one study has been performed to determine the values of Pd in healthy Silesian and Polish primitive horses [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…[5] A study in dogs found higher Pd values predictive of PAF recurrence after cardioversion. [6] High Pd values have also been found in patients with metabolic syndrome and HT risk. [7] Atrial dilation and atrial interstitial fi brosis have been recognized in atrial remodeling; these changes involve the renin-angiotensin system, which is already known to be part of the pathophysiology of hypertension, through the profi brotic effect of angiotensin II.…”
Section: Introductionmentioning
confidence: 99%